Attitudes and willingness to donate blood among gay and bisexual men in Australia. Issue 5 (2nd May 2020) - Clackett, Shawn; Seed, Clive R.; Prestage, Garrett; Hammoud, Mohamed A.; Hoad, Veronica; Saxton, Peter; Haire, Bridget; Holt, Martin; Jin, Fengyi; Bourne, Adam; Maher, Lisa; Kaldor, John
Abstract : BACKGROUND: Men who have sex with men in Australia are currently ineligible to donate blood (are "deferred") for 12 months since last oral or anal sexual contact with another man. In Australia and overseas, there has been limited research on attitudes and perceptions related to blood donation in this population. STUDY DESIGN AND METHODS: Questions on blood donation histories and attitudes toward the deferral policy were included in the questionnaire of an online prospective cohort of gay and bisexual men (GBM) living in Australia. RESULTS: In 2018, 1595 GBM responded to the survey. In this sample, 28.7% reported previously donating blood. Among the remaining men who had never donated blood, 64.5% expressed an interest in doing so. Nearly all men indicated they were not willing to abstain from sex with another man for 12 months in order to donate, and the vast majority believed the rule was unfair, too strict, and homophobic. Three‐quarters (77.7%) said that if the policy changed, they would likely donate blood. Age and openness about oneʼs sexuality were independently associated with oneʼs willingness to donate blood in the absence of the deferral. CONCLUSION: There was a high level of willingness and desire to donate blood among GBM. However, rather than abstaining from sex in order to donate, many men comply with the deferral policy and do not donate. A less conservative deferral policy may increase donations from GBM.